Identification of premalignant target cells using a mouse model of radiation-induced acute myeloid leukemia - Liu, Xiangfei, author; Ullrich, Robert L., advisor; Weil, Michael M., committee member; Ray, F. Andrew, committee member; Bamburg, James, committee member; Avery, Anne C., committee member (Colorado State University. Libraries, 2010)
Acute myeloid leukemia (AML) is believed to arise from the clonal expansion of a malignantly transformed blast cell. Whether spontaneous AML arises from a hematopoietic stem cell (HSC) or a more restricted progenitor of myeloid lineage is an area of active investigation. Much less is known about which cell types give rise to radiation-induced or radiotherapy-related AML. We are exploring this question using a mouse model of radiation-induced AML. Several mouse strains including CBA/CaJ are susceptible to radiation-induced AML whereas other strains are resistant. In murine radiation-induced AML the PU.l (Sfpil) gene behaves as a classic tumor suppressor gene. In most murine myeloid leukemias, there is a deletion in chromosome 2 encompassing the PU.l gene. The second ‘hit’ is generally a point mutation in the remaining PU.l allele. We used the PU.l deletion as an early marker for potential radiation-induced AML, and performed immunophenotyping combined with fluorescent in situ hybridization (immunoFISH) to study the persistence of this AML initiating lesion in myeloid and lymphoid lineages. Bone marrow cells were harvested from CBA/CaJ mice irradiated with 3 Gy of 137Cs y-rays 1, 3 and 6 months post-radiation and assayed by immunoFISH for PU.l deletions and cell differentiation markers. We demonstrated that the frequency PU.l deletions were similar in different cell types 1 month after irradiation but increased in the myeloid lineage and decreased in the lymphoid lineage at 3 and 6 months post-irradiation. PU.l deletions were only found in myeloid but not in lymphoid lineages in mice with radiation-induced AML. These results indicate that radiation-induced AML is likely to originate from the more restricted progenitor of the myeloid lineage. Immunostaining the mouse bone marrow cells with a panel of cell differentiation markers, we were able to isolate phenotypically defined hematopoietic stem cells and progenitor subpopulations. In future experiments, studying cytogenetic events in those particular bone marrow subpopulations will help achieve a better understanding on pathogenesis of radiation-induced AML. Identifying a small fraction of bone marrow cells bearing point mutations in the remaining PU.l gene remained as a technical challenge to our study of radiation-induced AML. We assessed a novel in situ hybridization approach that employs padlock probes as a potential tool to detect a PU.l point mutation and found it would only be useful if modifications were made to increase the fidelity of this technology.
Covers not scanned.
Keywords: Acute myeloid leukemia -- Animal models; Leukemia, Radiation-induced -- Animal models